1995
DOI: 10.1111/j.1440-1630.1995.tb01323.x
|View full text |Cite
|
Sign up to set email alerts
|

Hospice and palliative care: A Delphi survey of occupational therapists' roles and training needs

Abstract: This paper describes the use of the Delphi survey method to identify the roles and training needs of occupational therapists working in the field of hospice and palliative care in Australia. The study was conducted in 1993 using a purposive sample of 47 occupational therapists. The survey consisted of three consecutive questionnaires and five in‐depth interviews. The results indicated that there is a role for occupational therapy in this new and expanding field, and that occupational therapists need to promote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0
1

Year Published

1998
1998
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 9 publications
1
25
0
1
Order By: Relevance
“…Gammage, McMahon, and Shanahan (1976) proposed that occupational therapy has a unique role in supporting clients who are dying, as therapists: assist clients to adjust to the loss of old occupational roles and the facilitation of new ones, adapt activities and the environment to reflect the client's changing functional status, support clients through active listening, and foster the maintenance of client dignity and self-worth. Dawson and Barker (1995) further identified three main categories with respect to the therapist's role at end-of-life: problem-solver, educator/teacher, and networker/communicator. Several articles have suggested that fostering quality-of-life is a major focus for occupational therapy in this area of care (Egan, 2003;Picard & Magno, 1982;Pizzi, 1984;Nelson Tigges & Sherman, 1983;vanderPloeg, 2001).…”
Section: The Role Of Occupational Therapy At End-of-lifementioning
confidence: 99%
See 2 more Smart Citations
“…Gammage, McMahon, and Shanahan (1976) proposed that occupational therapy has a unique role in supporting clients who are dying, as therapists: assist clients to adjust to the loss of old occupational roles and the facilitation of new ones, adapt activities and the environment to reflect the client's changing functional status, support clients through active listening, and foster the maintenance of client dignity and self-worth. Dawson and Barker (1995) further identified three main categories with respect to the therapist's role at end-of-life: problem-solver, educator/teacher, and networker/communicator. Several articles have suggested that fostering quality-of-life is a major focus for occupational therapy in this area of care (Egan, 2003;Picard & Magno, 1982;Pizzi, 1984;Nelson Tigges & Sherman, 1983;vanderPloeg, 2001).…”
Section: The Role Of Occupational Therapy At End-of-lifementioning
confidence: 99%
“…Many of the articles indicated that the role of occupational therapy in end-of-life settings is not clear-cut; roles can overlap with other members of the hospice team, making it difficult to discern occupational therapy's unique contribution (Dawson & Barker, 1995). Conversely, the contribution of occupational therapy at end-of-life can also be depicted as focusing on very particular areas of care.…”
Section: The Role Of Occupational Therapy At End-of-lifementioning
confidence: 99%
See 1 more Smart Citation
“…48 This method is useful in situations where frequent clinical or practical judgments are encountered, yet incomplete published research exists to provide evidence-based decision making. [48][49][50] Because identification of content experts is essential, we targeted first or last authors of published studies that examined or developed prescriptive CPRs. We reasoned that, if an individual published one or more prescriptive CPR articles in the peer-reviewed literature, this person could provide useful feedback in a consensus-based format.…”
Section: Assessment Of Face Validity and Consensus Assessmentmentioning
confidence: 99%
“…1995). The study was conducted in 1994 and involved a Delphi survey on the roles and training needs of occupational therapists working in this field (Dawson & Barker, 1995). The results of this study indicated that all participants ( n = 47) identified a need for continuing education, preferably by external studies.…”
Section: Introductionmentioning
confidence: 99%